Perkembangan Konsep Open Radio Access Network (O-RAN) dalam Arsitektur Jaringan Seluler Modern: Tinjauan Literatur - Taura Ramadhani; Yulindon Yulindon (Kampus Akademik Publiser, 2026)
The development of cellular networks toward 5G and 6G introduces new challenges related to flexibility, efficiency, and interoperability in the Radio Access Network (RAN) architecture. Traditional RAN architectures, which are monolithic and proprietary in nature, are considered insufficient to meet the increasingly complex demands of modern communication networks. Therefore, the concept of Open Radio Access Network (O-RAN) has emerged as a solution through an open, distributed, and virtualization-based approach. This study aims to examine the development of the O-RAN concept in modern cellular network architectures using a literature review method with a qualitative approach. The research data were obtained from 10 reputable international journals published between 2020 and 2025 and analyzed using descriptive, comparative, and critical approaches. The results show that O-RAN represents a significant evolution from previous RAN architectures by improving network flexibility and interoperability through the implementation of open interfaces and the multi-vendor concept. The integration of supporting technologies such as Software Defined Networking (SDN), Network Function Virtualization (NFV), and Artificial Intelligence/Machine Learning (AI/ML) also enhances network efficiency, automation, and adaptive capabilities in real-time. Furthermore, several implementation studies indicate that O-RAN is capable of delivering competitive network performance while supporting deployment flexibility for 5G networks and future 6G development. However, the implementation of O-RAN still faces several challenges, including system integration complexity, interoperability among vendors, high computational requirements, and network security issues. This study contributes a comprehensive literature synthesis regarding the evolution, supporting technologies, implementation challenges, and future development directions of O-RAN in modern cellular networks. The findings are expected to serve as a reference for developing more open, flexible, adaptive, and sustainable cellular network architectures.